Website System Design Using Agile Kanban Based On QR Code - Purwanto, Alton Gunawan; Wijaya, Ricky Yohanes; Timotius, Timotius; Trisno, Indra Budi (JISA(Jurnal Informatika dan Sains), 2022)
Business developments that occur today cannot be separated from the role of technology and information systems. The system that will be discussed in this journal is a Web-based Restaurant System that uses a QR code. This system will handle at least 5 types of users, namely admin, waiter, chef, cleaning service, and customers where the five kind of users have different access rights. Restaurant information systems using this QR Code can speed up performance in ordering menus, serving ordered dishes, paying bills to customers and cleaning tables after use. The use of the QR code itself is very suitable in the restaurant business and marketing practices because of its advantages, namely being mobile fried and easy to get information. This will improve the quality of the restaurant in terms of service and time. This Web-Based Restaurant Menu Ordering Application is designed using web programming languages, namely PHP. For the database, it will use MySQL and the system development method will use the Agile Kanban method which can help an organization produce software that has been tested and is ready to use. The results of the system design will be in the form of a comparison table for the old and new systems depicted by the PIECES table, then UML for system modeling, and website interface. The system created will help in reducing the amount of paper used for order receipts. In addition, users can also order menus during the COVID-19 pandemic with restaurants that use this system.